Impact of Gut Dysbiosis on Child Development by Caesarean Section - Stephanie Kartjito, Melissa; Nurjannah, Aisyah (Ridwan Institute, 2023)
Caesarean delivery is an important medical procedure, and it is important to understand how this surgery may affect the balance of the child's gut microbiota. This study aims to determine the impact of gut dysbiosis on growth and development for children with Caesarean section. The research method used in this study is a literature study method with a qualitative approach, namely data collection by understanding and studying theories from various literatures related to the research. The results showed that gut dysbiosis can lead to digestive disorders, impaired nutrient absorption, and impaired physical growth. The compromised composition of the gut microbiota leads to a weakened immune system that can make children susceptible to infections and diseases, hindering their overall growth. Thus, medical and nutritionist care is needed to overcome the negative effects of gut dysbiosis in children born by caesarean section.